A Population-Based Model of the Temporal Memory in the Hippocampus - Oprisan, Sorinel A.; Buhusi, Mona; Buhusi, Catalin V. (Frontiers in Neuroscience, 2018)
Spatial and temporal dimensions are fundamental for orientation, adaptation, and survival of organisms. Hippocampus has been identified as the main neuroanatomical structure involved both in space and time perception and their internal representation. Dorsal hippocampus lesions showed a leftward shift (towards shorter durations) in peak-interval procedures, whereas ventral lesions shifted the peak time towards longer durations. We previously explained bluehippocampus lesion experimental findings by assuming a topological map bluemodel of the hippocampus with shorter durations memorized ventrally and longer durations more dorsal. blueHere we suggested a possible connection between the abstract topological maps model of the hippocampus that stored reinforcement times in a spatially ordered memory register and the ``time cells'' of the hippocampus. In this new model, the time cells provide a uniformly distributed time basis that covers the entire to-be-learned temporal duration. We hypothesized that the topological map of the hippocampus stores the weights that reflect the contribution of each time cell to the average temporal field that determines the behavioral response. The temporal distance between the to-be-learned criterion time and the time of the peak activity of each time cell provides the error signal that determines the corresponding weight correction. Long-term potentiation/depression could enhance/weaken the weights associated to the time cells that peak closer/farther to the criterion time. A coincidence detector mechanism, possibly under the control of the dopaminergic system, could be involved in our suggested error minimization and learning algorithm.